PENGARUH METODE MIND MAPPING TERHADAP PERKEMBANGAN KOGNITIF SISWA PADA PEMBELAJARAN IPS KELAS V MI MUHAMMADIYAH 03 TAKERHARJO - Nita Risma Wahyuni; Nanang Khoirul Umam; Arya Setya Nugroho (Nusantara Hasana Journal, 2023)
This study aims to determine the effect of the Mind mapping method on the cognitive development of students in social studies learning class V MI Muhammadiyah 03 Takerharjo, in the 2020/2021 academic year. Method The research method used in collecting research data is the method experiment with Pre-test - Post-test Control Group Design. Subject in this study were students of class V MI Muhammadiyah 03 Takerharjo with as many as 20 students consisting of 10 participants VA class students and 10 VB class students. Data collection techniques and The instrument used is a validation sheet, validity test, test normality, reliability test, homogeneity test, T test and ability test cognitive. Based on the analysis of research data obtained the findings: the influence of the Mind Mapping method on students' cognitive development in class V social studies learning at MI Muhammadiyah 03 Takerharjo. Proven with the Paired Sample T test is significant based on the output table these statistics, shows a significance value of 0.001 <0.05 at experimental group and 0.139 > 0.05 control group. Then, can it is stated that H0 is accepted meaning that there is no effect on the control class because they were not given treatment. While in the experimental class given the treatment stated, H0 was rejected, meaning that there was an effect Mind Mapping method on students' cognitive development in class V social studies learning at MI Muhammadiyah 03 Takerharjo which is used as the research sample.